Juveniles at risk a plea for preventive justice - Slobogin, Christopher, 1951-; Fondacaro, Mark R., 1957- (New York ; Oxford : Oxford University Press, 2011)
In this book, Slobogin and Fondacaro present their vision for a new juvenile justice system, founded on the evidence at hand and promoting the principles of rehabilitation and reintegration into society. The authors develop their juvenile justice policy proposals effectively by carefully addressing the problems with past policy approaches.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Juvenile delinquency -- United States; Juvenile justice, Administration of -- United States; Juvenile delinquents -- Rehabilitation -- United States